Facilitating higher education growth through fundraising and philanthropy - Alphin, Henry C., Jr., 1977- (2016)
"This book explores current and emergent approaches in the financial development and sustainability of higher education institutions through altruistic actions and financial assistance, featuring global perspectives on the economics of philanthropy in educational settings and subsequent growth and development within these environments"--
Studying Philanthropy and Fundraising in the Field of Higher Education : A Proposed Conceptual Model / Roy Y. Chan -- Philanthropy and the Character of the Public Research University : The Intersections of Private Giving, Institutional Autonomy, and Shared Governance / Larry Cata Backer, Nabih Haddad -- Tweeting for Donors : How Institutions of Higher Education Use Social Media to Raise Funds / Leigh N. Hersey -- Senior Leaders as Effective Fundraisers : A Toolbox for Dealing with Complexities in the New Ecology / Morgan R. Clevenger -- Higher Education and Philanthropy Potential in the GCC States : Analysis of Challenges and Opportunities for FDI and Venture Philanthropy in the MENA Region / Henry C. Alphin Jr., Jennie Lavine -- Rebirth of a Program via Community, Industry, and Philanthropic Support / Cathleen B. Ruch -- Unequal Partnerships? : Dynamics of Collaboration between U.S. Foundations and African Universities / Fabrice Jaumont -- Islamic Philanthropy and Higher Education : Re-imagining Tradition to Meet Contemporary Challenges / Sabithulla Khan -- Effective Approaches in Higher Education Development : A Survey in Fundraising Best Practices / Andrew A. Shafer -- The Role of Philanthropy on the Strategic Planning Process of a Selective Liberal Arts and Science College / Wayne P. Webster, Rick C. Jakeman, Susan Swayze -- The Role of Corporate and Foundation Relations Development Officers / Morgan R. Clevenger, Cynthia J MacGregor -- Alumni Giving and Social Exchange : A Study of Alumni Giving Behavior / Lauren E.B. Dodge.
Includes bibliographical references (pages 324-362) and index.
Keywords: Education, Higher -- Finance; Universities and colleges -- Finance; Educational fund raising; Charitable uses, trusts, and foundations